DESIGNING WRITING MATERIAL OF SHORT STORY THROUGH SHOW NOT TELL MODEL AT SMA XAVERIUS LUBUKLINGGAU - Yohana Satinem; J. Juwati (Universitas Sembilanbelas November Kolaka, 2017)
The aim of this research was to develop writing material of short story by using Show Not Tell (SNT). The result from this research hopefully able to use by students’ class X SMA Xaverius Lubuklinggau in learning Short Story. Writing short story is one activity that must do to inculcate the students’ creativities to explore their imagination and intuition related phenomenon that have done in their daily life trough language media. Method that used in this research was research and development. Therefore developing of material in this research combined developing model Jolly and Bolito, developing model Dick, Carey and Carey. The steps of the development of teaching materials in this study were 1) identification of needs; 2) Exploration material needs; 3) Realization contextual teaching materials; 7) Revised modules based on the results of the validation of a team of experts / specialists; 8) The field trials of the 25 students. Thus, research and development were process to develop and validate a product of education. Furthermore, data collection and data analysis in this study using the technique of questionnaires, interviews, and tests. From the data obtained information about the highest score on the pretest was 85 the highest value and the lowest value was 40, whereas in posttest, the highest value was 95 and the lowest value was 60. That is, there was an increase in the ability of students after using the results of the development of teaching materials.